The effective ways of experiential learning in education performance among Generation Z - Aris, Amir; Yahaya, Siti Norbaya; Zainal Abidin, Nur Haziqah; Bakar, Mohd Hafiz; Abdullah, Nor Hazana (Research and Scientific Innovation Society, 2026)
Experiential learning has been around for a long time and Malaysia still uses this learning system. It is because this method of learning through experience can help Generation Z to continue studying to a higher level easily. In this research, the researcher intended to study the effective ways of experiential learning in education performance among Generation Z in Malaysia. Blended learning, active learning and critical thinking is identified as effective ways of experiential learning in education performance among Generation Z in Malaysia. In addition, descriptive and explanatory studies are used in this research. This study uses a quantitative approach. Generation Z will be surveyed to collect primary data by disseminating questionnaires. Furthermore, sampling based on probability will be used to select 384 respondents. To assure data consistency, a pilot test and reliability analysis will be conducted. Statistical Package for the Social Sciences (SPSS) will also be used to analyze the results obtained from respondents. Based on the findings, blended learning, active learning, and critical thinking have significant relationships with the effective ways of experiential learning in education performance among Generation Z in Malaysia, and blended learning is the most effective way of experiential learning in education performance among Generation Z in Malaysia. Researchers may utilize the newly suggested conceptual framework to conduct their research or incorporate additional variables into their study.